THE MOTHERS AND TODDLERS PROGRAM, AN ATTACHMENT-BASED PARENTING INTERVENTION FOR SUBSTANCE-USING WOMEN: RESULTS AT 6-WEEK FOLLOW-UP IN A RANDOMIZED CLINICAL PILOT - SUCHMAN, NANCY E. (2011)
Previously, we reported posttreatment findings from a randomized pilot study testing a new attachment-based parenting intervention for mothers enrolled in substance-use treatment and caring for children ages birth to 3 years (N.E. Suchman, C. DeCoste, N. Castiglioni, T. McMahon, B. Rounsaville, & L. Mayes, 2010). The Mothers and Toddlers Program (MTP) is a 12-session, weekly individual parenting therapy that aims to enhance maternal capacity for reflective functioning and soften harsh and distorted mental representations of parenting. In a randomized pilot study, 47 mothers who were enrolled in outpatient substance-abuse treatment and caring for children between birth and 3 years of age were randomized to the MTP versus the Parent Education Program (PE), a comparison intervention that provided individual case management and developmental guidance. At the end of treatment, mothers in the MTP condition demonstrated better reflective functioning, representation quality, and caregiving behavior than did mothers in the PE condition. In this investigation, we examined whether the benefits of MTP at posttreatment were sustained at the 6-week follow-up. Recently, we also identified two components of parental reflective functioning: (a) a self-focused component representing the parent's capacity to mentalize about strong personal emotions (e.g., anger, guilt, or pain) and their impact on the child and (b) a child-focused component representing the parent's capacity to mentalize about the child's emotions and their impact on the mother (N. Suchman, C. DeCoste, D. Leigh, & J. Borelli, 2010). In this study, we reexamined posttreatment outcomes using these two related, but distinct, constructs.